Effect of short-term exposure to indoor particulate matter on noctunal blood pressure dipping among hypertensive adults in ibadan: a pilot study. (25th November 2020) - Adeoye, A.M; Fakunle, A; Aderonmu, O; Tayo, B
Abstract: Introduction: While blunted nocturnal blood pressure is a major risk factor for cardiovascular events, limited information exist on the association between indoor particulate and circadian blood pressure variation. We report the association of short-time exposure to PM2.5 and PM10 with blunted nocturnal blood pressure among hypertensive adults in Ibadan. Purpose: This study was to determine the association between short time exposure to air particulates and blunted nocturnal blood pressure among people of African descent. Methods: We conducted a cross-sectional study among fifty hypertensive cases attending our University College Hospital. A 24-hours blood pressure (BP) monitoring was carried out at the same time as indoor particulate matter monitoring in their homes. Exposure to indoor fine particles (PM2.5) and thoracic particles (PM10) was estimated using a real-time particle counter and compared to the World Health Organization (WHO) 24-hours threshold of 25 μg/m 3 and 50 μg/m 3 for PM2.5 and PM10 respectively. All monitoring was carried out over a 24-hours period during the wet season. Linear regression model was fitted to determine predictors of non-dipping hypertension. Results: Of the 50 hypertensive patients studied, 5 (10.0%), 39 (78.0%), 6 (12.0%) were reverse dippers, non-dippers and dippers respectively. The mean indoor PM2.5 (44.17±19.18 μg/m 3 ) and PM10 (60.10±27.13 μg/m 3 ) among the non-dippers were significantly higher than values obtained among dippers (PM2.5 = 22.97±10.19 μg/m 3 ; PM10 = 29.51±12.74 μg/m 3 ); p<0.0001, and the WHO threshold limit. More non-dippers than dippers (54.5% vs 37.8%) used unimproved fuel such as firewood for cooking. PM10 was an independent predictors of non-dipping status in our regression analysis. Conclusion: Short-term exposure to indoor PM air pollution was associated with blunted nocturnal blood pressure. Therefore air pollution reduction strategies through improved cooking pattern is advocated in order to prevent future cardiovascular events. Funding Acknowledgement: Type of funding source: None